Neutron transmission measurements at nELBE - Junghans Arnd; Beyer Roland; ClauBner Jürgen; Kögler Toni; Urlass Sebastian; Bemmerer Daniel; Ferrari Anna; Schwengner Ronald; Wagner Andreas; Dietz Mirco; Frotscher Axel; Grieger Marcel; et al. (EPJ Web of Conferences, 2020)
Neutron total cross sections are an important source of experimental data in the evaluation of neutron-induced cross sections. The sum of all neutron-induced reaction cross sections can be determined with a precision of a few per cent in a relative measurement. The neutron spectrum of the photoneutron source nELBE extends in the fast region from about 100 keV to 10 MeV and has favourable conditions for transmission measurements due to the low instantaneous flux of neutrons and low gamma-flash background. Several materials of interest (in part included in the CIELO evaluation or on the HPRL of OECD/NEA) have been investigated: 197Au [1, 2], natFe [2], natW [2], 238U, natPt, 4He, natO, natNe, natXe. For gaseous targets high pressure gas cells with flat end-caps have been built that hold up to 200 bar pressure. The experimental setup will be presented including results from several transmission experiments and the data analysis leading to the total cross sections will be discussed.